One visit endodontic as a treatment option during the pandemic: One visit endodontic sebagai sebuah pilihan perawatan di masa pandemi - Dewi Krisyanti; Noor Hikmah (Makassar Dental Journal, 2024)
This case report aims to describe one visit endodontic treatment as an option for teeth that need root canal treatment, espe-cially during the pandemic. Teledentistry was performed as the initial stage for history taking, DHE and informed consent prior to the patient's visit to the clinic for treatment on a 14-year-old patient with complaints of a decayed and painful lower back tooth. Thermal and percussion tests were positive, palpation was negative. Radiographs showed caries almost reaching the pulp with periapical radiolucency. Single length preparation technique became the treatment of choice during the pandemic. One visit endodontic treatment is effective in overcoming the patient's subjective and objective complaints. It is concluded that OVE treatment is one of the root canal treatment options, especially during a pandemic with a high success rate.